(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Social behavior of man with all the diversity of specific historical conditions and place of the person in a society is caused, first of all by an opportunity communication of people with the help of language. Language as the direct embodiment of thinking materializes the process and result of man’s cognitive activity and fixes in its form is any individual act of cognition as a social category. Verbal communication is in this sense a condition for the existence of man in a society that gives him the opportunity to develop material production as a basis all life.